2019
DOI: 10.1051/eas/1982035
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum transport in accretion disks: a hydrodynamical perspective

Abstract: The radial transport of angular momentum in accretion disk is a fundamental process in the universe. It governs the dynamical evolution of accretion disks and has implications for various issues ranging from the formation of planets to the growth of supermassive black holes. While the importance of magnetic fields for this problem has long been demonstrated, the existence of a source of transport solely hydrodynamical in nature has proven more difficult to establish and to quantify. In recent years, a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 99 publications
(119 reference statements)
0
20
0
Order By: Relevance
“…Hydrodynamic angular momentum transfer mechanisms generally rely on the onset and sustenance of turbulence, which is closely related to the hydrodynamic stability of the disk [see recent reviews ( 14 , 15 )]. When ignoring thermodynamics, the stability of a disk is described by the well-known Rayleigh criterion ( 16 ), which states that a rotating, inviscid system is linearly stable to axisymmetric perturbations as long as j increases radially outward (∂ j / ∂R > 0) ( Fig.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrodynamic angular momentum transfer mechanisms generally rely on the onset and sustenance of turbulence, which is closely related to the hydrodynamic stability of the disk [see recent reviews ( 14 , 15 )]. When ignoring thermodynamics, the stability of a disk is described by the well-known Rayleigh criterion ( 16 ), which states that a rotating, inviscid system is linearly stable to axisymmetric perturbations as long as j increases radially outward (∂ j / ∂R > 0) ( Fig.…”
Section: Theorymentioning
confidence: 99%
“…Three purely hydrodynamic instabilities have recently been considered for PPDs: the vertical shear instability (VSI), the related processes of convective overstability (COS) and subcritical baroclinic instability (SBI), and the zombie vortex instability (ZVI). A detailed discussion for each of the instabilities is beyond the scope of this review; readers are referred to ( 14 , 15 ) for further information. Here, we summarize the main requirements for each instability to operate, their possible existence in PPDs (see Fig.…”
Section: Theorymentioning
confidence: 99%
“…This however would require that a robust turbulence-driving mechanism unrelated to the MRI, such as a hydrodynamic instability, is excited in Keplerian discs. Such a mechanism, if any, remains elusive (Fromang & Lesur 2017).…”
Section: The Diverse Challenging Complexity Of Large-scale Dynamosmentioning
confidence: 99%
“…For ∇ ad ∼ 0.285, and the opacity prescription of Bell & Lin (1994), this condition can be satisfied in large parts of the disk, including at 0.1 AU. While these models were set aside for a while due to conflicting numerical results (Klahr 2007), more recent studies, for example Rafikov (2007); Lesur & Ogilvie (2010) ;Fromang & Lesur (2019); Pfeil & Klahr (2019), showed that vertical convective instability in disks cannot yet be excluded as a plausible heat and angular momentum transport mechanism.…”
Section: The Effect Of Disk Entropy On Envelope Growthmentioning
confidence: 99%